Psychometric properties of the Adolescent Motor Competence Questionnaire for Norwegian adolescents - Lorås, Håvard; Haga, Monika; Hagen, Ruben Vist; Bjerke, Øyvind; Timler, Amanda; Sando, Ole Johan (Frontiers in Psychology, 2024)
The objective of this study was to examine the psychometric properties of the Adolescent Motor Competence Questionnaire (AMCQ) for Norwegian adolescents. To this end, a sample of 349 Norwegian-speaking adolescents (13-16 years old) were recruited and completed the AMCQ. Initial results showed that Confirmatory Factor Analysis (CFA) did not indicate statistical support for previous statistical models reported in the literature. Further analysis indicated factorial validity for a novel three-factor model identified through exploratory factor analysis, encompassing measures of fine motor skill (α = 0.65), gross motor skill (α = 0.74), and activities of daily living (ADL; α = 0.79) with acceptable internal consistency coefficients. Subsequent analysis indicated indices of measurement invariance in the study sample, as males rated their competence higher compared to females in 19 of the 27 items, and better model fit was obtained for the female adolescents. Strong invariance was tenable, and no factor mean differences were found across older and younger adolescents or across BMI scores. Overall results thus suggested that the AMCQ has acceptable psychometric properties and can be confidently used in further work with perceived motor competence in Norwegian 13-16-year-old adolescents.